Gagasan konseptual supervisor pendidikan tentang pembelajaran inovatif model lingkungan sekitar sebagai Sumber belajar guna meningkatkan mutu guru dalam mengajar di MIS Meunasah Teungoh - Azizah, Azizah (Universitas Serambi Mekkah, 2020)
The purpose of this study is to improve the ability of teachers to use the school environment as a source of learning through Teacher Working Group (KKG) discussions and to improve learning methods ap-plied in schools so as to increase creativity, motivation and student learning outcomes. The subjects of this School Action Research are all class teachers at MIS Meunasah Teungoh in the 2019/2020 Academ-ic Year with a total of 18 teachers. The number of male teachers is 5 people and female teachers are 13 people. This School Action Research was conducted in the 2019/2020 Academic year. This School Ac-tion Research was conducted in 3 months, from August to October 2019 in odd semester. The data ob-tained came from MIS Meunasah Teungoh class teacher in 2019/2020 Academic Year. This research is a School Action Research consisting of two cycles and each cycle consists of two meetings. The data collection technique is carried out by supervising the school principal for the teacher or conducting class visits, evaluating the teacher's preparation for taking part in the guidance of learning to use Information and Communication Technology (ICT). Assessing the results of observations, learning scenarios and learning implementation in utilizing the school environment as a source of learning through the Teacher Working Group (KKG) discussion. Data collection techniques are through the supervision list of princi-pals. Data analysis was performed descriptively qualitatively by observation and reflection through ob-servation of learning scenarios and learning implementation. The research procedure consisted of Cycle I and Cycle II. The results showed, the average value of the increase in the ability of teachers to use the school environment as a source of learning is the average value of the observation results of the discus-sion activity 79.85 in Cycle I to 89.00 in Cycle II there was an increase of 9.15. In the activity of prepar-ing learning scenarios the average value of 80.71 in Cycle I to 91.42 in Cycle II there was an increase of 10.71. Learning activities or in the teaching and learning process the average value of 77.61 in Cycle I to 87.14 in Cycle II, there was an increase of 9.53.